The Church of England and Christian Antiquity: The Construction of a Confessional Identity in the 17th Century. By Jean-Louis Quantin - Brydon, Michael (The journal of theological studies, 2009)
Marcantonio De Dominis, the Roman Catholic Archbishop of Spalato, who fled to England in 1616 and subsequently joined the Church of England, sought to publicize abroad the virtues of his newly found ecclesiastical communion through his De Republica ecclesiastica. The frontispiece to this book shows De Dominis, surrounded by folios of the Fathers, busy transcribing a passage from Cyprian. This charming picture appears to encapsulate the belief that Anglicans have a distinctive ecclesiology based on Scripture, but interpreted through the writings of the undivided church of the first four centuries. Such a reading, however, is shown to be deeply anachronistic by this thoroughly researched work.